2011
DOI: 10.1111/j.1467-6435.2011.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Integration, Social Networks and Economic Success of Immigrants: A Case Study of the Turkish Community in Berlin

Abstract: SUMMARY The observation that some immigrants choose not to integrate into the host society has caused political controversies across European states. This paper hypothesizes that immigrants can exploit social networks of different scales in order to substitute for costly integration. Using a novel dataset of Turkish households in Berlin, which was specifically collected for this analysis, we investigate the determinants of integration as well as the impact of integration and networks on households' economic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 41 publications
(46 reference statements)
0
21
0
2
Order By: Relevance
“…2013b). Danzer and Ulku () found that immigrant's ethnic and familial networks increase the income of unintegrated migrants, especially for poorer, uneducated households. Therefore, it can be assumed that immigrant entrepreneurs will find it easier to operate in an open economy framework and therefore:…”
Section: Entrepreneurshipmentioning
confidence: 99%
“…2013b). Danzer and Ulku () found that immigrant's ethnic and familial networks increase the income of unintegrated migrants, especially for poorer, uneducated households. Therefore, it can be assumed that immigrant entrepreneurs will find it easier to operate in an open economy framework and therefore:…”
Section: Entrepreneurshipmentioning
confidence: 99%
“…Recent papers have described whether and how strongly immigrants identify with the culture of the host country (Bisin et al, ; Drever, ; Dustmann, ; Manning and Roy, ). Beside subjective self‐identification, some other measures of integration in the literature are language (Bauer et al, ; Dustmann, ; Lazear, ), citizenship (Danzer and Ulku, ), or composite metrics (Constant and Zimmermann, ).…”
Section: Introductionmentioning
confidence: 99%
“…This largely applies to migrants from these countries, too (Aelenei, Darnon, & Martinot, 2016;Arends-Tóth & van de Vijver, 2008; Ayçiçegi-Dinn & Caldwell-Harris, 2011). Interdependent family structures and extended social networks among migrants can provide greater social support, which has been shown to be a buffer for acculturative stressors (Danzer & Ulku, 2011) and a protective influence against delinquency (Le & Stockdale, 2005). Social support is supposed to be a general protective influence against delinquency (Stouthamer-Loeber et al, 2002) that might be even more important in collectivist cultures than in individualist cultures, which can only be checked via a cross-cultural comparative study.…”
Section: Protective Factors Sensitive To Cultural Socializationmentioning
confidence: 99%